Not Just Sea Turtles, Let's Protect Women Too: Invoking Public Morality Exception or Negotiating a New Gender Exception in Trade Agreements?. (26th February 2022) - Bahri, Amrita; Boklan, Daria
Abstract: The most common provisions we find in almost all multilateral, regional and bilateral trade agreements are the exception clauses that allow countries to protect public morals, humans, animals or plant health and life and conserve exhaustible natural resources. If countries can allow trade-restrictive measures that aim to protect these non-economic interests, is it possible to negotiate a specific exception to justify measures that are aimed at protecting women's economic interests as well? Is the removal of barriers that impede women's participation in trade any less important than the conservation of exhaustible natural resources such as sea turtles or dolphins? In that context, this article prepares a case for the inclusion of a specific exception that can allow countries to leverage women's economic empowerment through international trade agreements. This is done after carrying out an objective assessment of whether a respondent could seek protection under the existing public morality exception to justify a measure that is taken to protect women's economic interests.